Vierteljahrshefte für Zeitgeschichte (De Gruyter Oldenbourg, 2005)
Published since 1953 by the Institute for Contemporary History, the Quarterly Review of Contemporary History ranks among Germany's highest circulation academic journals. It is a forum for outstanding scholars from Germany and abroad to present their latest research findings on key problems of contemporary and very recent German and European history.